A fatal case of acute encephalopathy in a child due to coxsackievirus A2 infection: a case report - Nagai, Tomonori; Hanaoka, Nozomu; Katano, Harutaka; Konagaya, Masami; Tanaka-Taya, Keiko; Shimizu, Hiroyuki; Mukai, Toshiji; Fujimoto, Tsuguto (BMC infectious diseases, 2021)
Certain types of enteroviruses, including coxsackieviruses, cause encephalitis, and other neurological complications. However, these pathogens rarely cause fatal infections, especially in immunocompetent infants. In this study, we present a rare case of acute encephalopathy caused by coxsackievirus A2 (CV-A2), which progressed rapidly in a previously healthy female child. Based on our findings, we concluded that a previously healthy girl who had no immediate history of underlying medical condition were susceptible to death by acute encephalopathy due to CV-A2 infections. We proposed this conclusion because the patient's condition progressed rapidly in less than 2 h and eventually led to her death. This is the first report on an acute encephalitis-dependent death in a child due to CV-A2 infection.